Anti-Inflammatory and Antinociceptive Activities of Bufalin in Rodents - Lili Wen; Yang Huang; Xianbiao Xie; Wan Huang; Junqiang Yin; Wenqian Lin; Qiang Jia; Weian Zeng (Mediators of Inflammation)
The aims of this study were to evaluate the anti-inflammatory and analgesic effects of bufalin, a major component of “Chan-su.” We used a carrageenan-induced paw edema model to assess the anti-inflammatory activity of this compound, and Western blot analysis detected NF-κB signaling during this effect. The antinociceptive activities were evaluated by acetic acid-induced writhing, formalin, and hot-plate tests; open-field test investigated effects on the central nervous system. Our data showed that bufalin (0.3 and 0.6 mg/kg, i.p.) potently decreased carrageenan-induced paw edema. Bufalin down regulated the expression levels of nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) during these treatments. Further studies demonstrated that bufalin significantly inhibited the activation of NF-κB signaling. Bufalin also reduced acetic acid-induced writhing and the licking time in the formalin test and increased hot-plate reaction latencies. Naloxone pretreatment (2 mg/kg, i.p.) in the early phases of the formalin test and hot-plate test significantly attenuated the bufalin-induced antinociception effects, which suggests the involvement of the opioid system. A reduction in locomotion was not observed in the open-field test after bufalin administration. Taken together, bufalin treatment resulted in in vivo anti-inflammatory and analgesic effects, and bufalin may be a novel, potential drug for the treatment of inflammatory diseases.